(3-u)(3u-2)=0

Simple and best practice solution for (3-u)(3u-2)=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (3-u)(3u-2)=0 equation:


Simplifying
(3 + -1u)(3u + -2) = 0

Reorder the terms:
(3 + -1u)(-2 + 3u) = 0

Multiply (3 + -1u) * (-2 + 3u)
(3(-2 + 3u) + -1u * (-2 + 3u)) = 0
((-2 * 3 + 3u * 3) + -1u * (-2 + 3u)) = 0
((-6 + 9u) + -1u * (-2 + 3u)) = 0
(-6 + 9u + (-2 * -1u + 3u * -1u)) = 0
(-6 + 9u + (2u + -3u2)) = 0

Combine like terms: 9u + 2u = 11u
(-6 + 11u + -3u2) = 0

Solving
-6 + 11u + -3u2 = 0

Solving for variable 'u'.

Factor a trinomial.
(-3 + u)(2 + -3u) = 0

Subproblem 1

Set the factor '(-3 + u)' equal to zero and attempt to solve: Simplifying -3 + u = 0 Solving -3 + u = 0 Move all terms containing u to the left, all other terms to the right. Add '3' to each side of the equation. -3 + 3 + u = 0 + 3 Combine like terms: -3 + 3 = 0 0 + u = 0 + 3 u = 0 + 3 Combine like terms: 0 + 3 = 3 u = 3 Simplifying u = 3

Subproblem 2

Set the factor '(2 + -3u)' equal to zero and attempt to solve: Simplifying 2 + -3u = 0 Solving 2 + -3u = 0 Move all terms containing u to the left, all other terms to the right. Add '-2' to each side of the equation. 2 + -2 + -3u = 0 + -2 Combine like terms: 2 + -2 = 0 0 + -3u = 0 + -2 -3u = 0 + -2 Combine like terms: 0 + -2 = -2 -3u = -2 Divide each side by '-3'. u = 0.6666666667 Simplifying u = 0.6666666667

Solution

u = {3, 0.6666666667}

See similar equations:

| 9ln(x+18)-6ln(x)= | | y=4(0.5) | | -(4y-5)(5y-8)= | | X^2+3x=49 | | 6x^4+40x^3y-14x^2y^2=0 | | 21-4x=12-7x | | 15x=121 | | 2*1/3 | | x-10-4x=-25 | | 3+10+5y=20 | | 3x=2+1 | | 72=2+3a+2a | | 9x+x=9 | | 12x+3=2x+1 | | y+7x=16 | | 3(-25-6+8)= | | -9+5x+x=63 | | 2x+41+127=180 | | 7a-28b/a-4b | | 4(3x+2)(3x+2)=5 | | 46=3w^2+3w | | 5x5/7 | | 6x^2+12x-16=20 | | 15*m=42 | | 2x*2x+2x-12=0 | | -6(v+3)+3v+6=6v+8 | | 54x^2+48x+11=0 | | 315/x=4/16 | | .5x=1.56 | | 6+10x=-94 | | 2[7-6(1-n)]+9=-32+6[6(n+1)-3n] | | 2/7b=1/7 |

Equations solver categories